A near-infrared phosphorescent iridium(iii) complex for imaging of cysteine and homocysteine in living cells and in vivo. Issue 83 (14th November 2017) - Wu, Yongquan; Wu, Renmiao; Li, Huifang; Zeng, Hong; Li, Yuanyan; Wang, Qiuhong; Shi, Mei; Fan, Xiaolin
Abstract : A novel NIR-emitting iridium(iii ) complex was developed to detect Cys/Hcy levels in vitro and in vivo . Abstract : Based on the cyclization reaction of an aldehyde with an aminoalkyl thiol, a novel NIR-emitting iridium(iii ) complex (NIR-Ir ) showed off–on phosphorescent response toward Cys and Hcy, and was developed to detect Cys/Hcy levels in vitro and in vivo .